Biosynthesis of silver nanoparticles from the novel strain of Streptomyces Sp. BHUMBU-80 with highly efficient electroanalytical detection of hydrogen peroxide and antibacterial activity - Gupta R.K.; Kumar V.; Gundampati R.K.; Malviya M.; Hasan S.H.; Jagannadham M.V. (My University, 2025)
The use of a microbial supernatant has become a potential source for the eco-friendly and rapid synthesis of nanoparticles. In this study, we have targeted to synthesize silver nanoparticles (AgNPs) using extracellular secretion of Streptomyces sp. The strain was successfully isolated from the soil samples and identified as Streptomyces sp. BHUMBU-80 on the basis of morphological, biochemical and Phylogenetic analysis. The synthesized AgNPs was characterized using several modern characterizing techniques such as UV-vis Spectroscopy, FTIR spectroscopy, SEM, EDX spectroscopy, TEM, XRD and XPS. The presence of characteristics SPR band at 450 nm confirmed the synthesis of AgNPs. The FTIR spectra confirmed the involvement of various functional groups present in culture supernatant responsible for the reduction of Ag+ ions into Ag0. SEM and TEM analysis confirmed the presence of spherical AgNPs with an average size of 21 ± 1 nm. The XPS analysis confirmed the presence of two individual peaks which attributed to the Ag 3d3/2 and Ag 3d5/2 binding energies corresponding to the presence of metallic silver. The electrochemical studies of the green synthesized AgNPs using a glassy carbon electrode showed the superior electrocatalytic activity towards the reduction of H2O2. The calibration plot was established for H2O2 in the concentration range from 50 μM to 1000 μM with 50 μM detection limit, at a signal-to-noise ratio of 3 in a three-electrode cell with a Pt plate as the counter electrode. Additionally, the AgNPs also showed potent antibacterial activity against pathogenic bacteria like E. coli, and S. aureus. © 2017 Elsevier Ltd. All rights reserved.